Cardiac Tamponade as the Initial Presentation of Acute Myeloid Leukemia: A Case Report with Review of the Literature - Dillon Karmo; Adam Hafeez; Alexandra Halalau; Siddhartha Yadav (Case Reports in Oncological Medicine)
Acute myeloid leukemia (AML) is a complex disease with a variety of presentations. A large pericardial effusion is rare, occurring in less than 0.5% of all patients with AML prior to treatment. A 34-year-old male presented with dyspnea, malaise, and weight loss. On physical exam, he was noted to be hypoxic, tachypneic, tachycardic, and hypotensive. He had cervical lymphadenopathy and jugular venous distention. His WBC count was 110 bil/L with 33% blasts. Bone marrow biopsy confirmed AML with 60% blasts. Leukemic cells were also seen in the cerebrospinal fluid on lumbar puncture. An echocardiogram revealed a large pericardial effusion causing tamponade. He underwent emergent pericardiocentesis, and malignant cells were present in the pericardial fluid. Induction therapy with standard dose cytarabine and daunorubicin was initiated, and bone marrow biopsy 14 days later showed no residual AML. This case demonstrates the importance of a thorough evaluation of each organ system when caring for a patient with AML.